Analysis Study Of Leadership Strategies In Implementing Improvement Concept Quality In Higher Education - Suzanni, Suzanni (International Journal of Technology and Education Research, 2023)
The issue of quality in higher education is important to be made into a special study in an effort to improve education which will have an impact on Indonesia's development in various fields, because it is in higher education that policy makers, scientists, artists, and technological engineers should be born with no regard for intelligence, but more than that character building for the next generation of the nation in the future. Many factors make the quality of higher education low, one of which is the non-implementation of higher education quality assurance. Quality assurance itself should be a separate system that guarantees the continuity of quality higher education. According to Law no. 20 of 2003 concerning the National Education System, there are three components that regulate issues of quality assurance in higher education that currently exist, including the Ministry of National Education through the Directorate General of Higher Education, the National Education Standards Agency, and the National Accreditation Board. Each one should form a system that coordinates with each other, but in reality each seems to still stand alone. This problem will certainly have an impact on higher education as an autonomous institution that organizes higher education, the public who use higher education services, as well as the business and industrial world as users of higher education graduates. Higher education as an autonomous institution has the task of running an internal quality assurance system, reporting its internal quality assurance to the Director General of Higher Education to then carry out an external quality assurance system.